The Effect of Special Fartlek Style Exercises in Developing the Speed Endurance of First-Class Football Referees - Hussein, Mohammad Gheni (Indonesian Journal Publisher, 2024)
The research aimed to prepare exercises in the fartlek style to develop the speed endurance of first-class football referees. The researcher used the experimental method with the same design for one interconnected experimental group (pre-post), while the research sample included a sample of first-class referees (field referees and assistant referees) in Baghdad and accredited to the Central Iraqi Football Federation for the 2023-2024 football season, amounting to (30) referees who were chosen randomly, and special fartlek-style exercises were prepared at (3) training units per week for (8) weeks to develop the referees’ speed endurance and passing physical tests. After processing the data statistically, the researcher concluded that the experimental group had achieved a noticeable improvement in the speed endurance variable, due to the use of the fartlek method, as the results showed statistically significant differences between the pre- and post-measurements, in favor of the post-measurement. The researcher recommended the necessity of applying exercises specific to the fartlek method due to its effectiveness and its positive impact on football referees.